Equity in climate change : the great divide - Müller, B (Oxford Institute for Energy Studies, 2002)
There is a strongly held view in the policy analysis community and beyond that developing countries will play a significant role in determining the success of the multilateral climate change regime under the UN Framework Convention on Climate Change (FCCC). It is equally widely understood that, consequently, success will not be forthcoming unless the key concerns of these countries - particularly those pertaining to inequities - are sufficiently taken into account in the future development of the regime. In ‘Diagnosing the Divide,’ this study detects a clear North-South Divide in the views on the nature of the paramount climate change equity problem. In the Northern hemisphere, where the relevant discussion is spearheaded by non-government stakeholders (academic, EGO), it is regarded to be the issue of allocating emission mitigation targets; in the South, the concern - reflected by many governments - is above all about the discrepancy between the responsibility for, and the sharing of climate impact burdens. Acknowledging the importance for the global climate change regime to continue its efforts in avoiding and limiting future anthropogenic climate-related disasters, the second part of this study (‘Bridging the Divide: Redressing The Balance’) argues that we have passed the point where complete avoidance could have been assured, and that consequently the regime must face up to this inevitability and begin to prepare appropriate impact/disaster response measures. Given the existing threat, particular urgency is attached to a proposal for reform of the relevant disaster relief funding mechanism by creating an FCCC Climate Impact Relief (CIR) Fund to achieve an international relief system adequate to the challenge. Because this is to involve merely a more efficient funding mode, such a reform could be carried out with little or no additional costs (no ‘new money’), yet with significant benefits to the international community.